1997
DOI: 10.1016/s0014-5793(97)00311-6
|View full text |Cite
|
Sign up to set email alerts
|

The packaging capacity of adeno‐associated virus (AAV) and the potential for wild‐type‐plus AAV gene therapy vectors

Abstract: Because of its ability to integrate chromosomally and its non-pathogenic nature, adeno-associated virus (AAV) has significant potential as a human gene therapy vector. Here we investigate the maximum amount of DNA which can be inserted into the AAV genome and still allow efficient packaging into an infectious virus particle. Altered wild-type AAV genomes were constructed with inserts, which increased in size by 100 bp, ligated at map unit 96. These large wild-type-plus genomes were able to replicate and produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…High -titer rough ( nonpurified ) rAAV virus stocks were generated in a two -step process, using the complementor plasmid ins96 -0.8, and titered as described previously. 37,49 To generate purified rAAV virus the technique described by Auricchio et al 50 was used. Briefly, the virus solution treated by DNase I ( Promega Co., Madison, WI ) was incubated with 0.5% deoxycholic acid ( Sigma, St. Louis, MO ) for 30 minutes at 378C.…”
Section: Methodsmentioning
confidence: 99%
“…High -titer rough ( nonpurified ) rAAV virus stocks were generated in a two -step process, using the complementor plasmid ins96 -0.8, and titered as described previously. 37,49 To generate purified rAAV virus the technique described by Auricchio et al 50 was used. Briefly, the virus solution treated by DNase I ( Promega Co., Madison, WI ) was incubated with 0.5% deoxycholic acid ( Sigma, St. Louis, MO ) for 30 minutes at 378C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that up to 6.0 kb can be packaged into virus, but these 'over-sized' viruses were not infectious, 32 hence the common assumption is that the packaged genome must be limited to just 110% of wild-type AAV or no greater than ෂ5.1 kb. 33 This limited DNA insert size restricts the range of open reading frames which can be inserted for any given promoter and post-regulatory element and polyadenylation signal. 34 A secondary goal was to test the outer limits of AAV-2 genome size, while maintaining packaging and infectious efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…112,113 This small packaging size of AAV has always been thought to preclude its use for delivering genes larger than 5 kb, such as dystrophin and factor VIII, or the use of large regulatory elements to enhance or control transgene expression. Recently, a new approach has been developed to overcome this vector size limitation by exploiting the unique heterodimerization ability of AAV DNA.…”
Section: Split Vectorsmentioning
confidence: 99%